Simple test kit based on colorimetry for quantification of magnesium content in natural rubber latex by miniaturized complexometric titration without using masking agent. (May 2017) - Malahom, Nutthaporn; Jarujamrus, Purim; Meelapsom, Rattapol; Siripinyanond, Atitaya; Amatatongchai, Maliwan; Chairam, Sanoe
Abstract: A simple, low-cost and portable field test kit based on colorimetry with detection by naked eye was developed for determination of magnesium content in natural rubber latex (NRL). The miniaturized complexometric titration between Mg 2+ and EDTA without any masking agent was a key reaction in this development, which was designed according to the concept of green chemistry by reduction of waste generation and chemical and time consumption. The system enabled quantification of magnesium content in NRL at low concentration with the detection limit being <50 mg L −1, small sample volume uptake (0.18 g, sampling by a small spoon) and use of <1.5 mL reagent volume which was >70 times less than that applied in the conventional method. Moreover, with the presence of potential interference ions, greater selectivity towards magnesium was observed. Furthermore, the reagents used in our developed test kit were stable for >6 months at room temperature. The results obtained on real samples were in agreement with those obtained from the conventional complexometric titration (ISO 17403: 2014(E)) method. The proposed technique provides a low-cost, rapid, simple, selective and on-site analysis of magnesium content in NRL.